Female urethral diverticulum presenting with acute urinary retention: Reporting the largest diverticulum with review of literature - Pradhan, Manas Ranjan (Medknow Publications & Media Pvt Ltd, 2012)
Female urethral diverticulum is a rare entity with diverse spectrum of clinical manifestations. It is a very rare cause of bladder outlet obstruction and should be considered as a differential diagnosis in females presenting with acute urinary retention associated with a vaginal mass. Strong clinical suspicion combined with thorough physical examination and focused radiological investigations are vital for its diagnosis. Herein we report a case of giant urethral diverticulum presenting with acute urinary retention in a young female. It was managed by excision and urethral closure, and is the largest urethral diverticulum reported till date in the literature.